2008
DOI: 10.2353/ajpath.2008.070762
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Up-Regulates Angiotensin I-Converting Enzyme (ACE), but Down-Regulates ACE2 via the AT1-ERK/p38 MAP Kinase Pathway

Abstract: The recent discovery of the angiotensin II (Ang II)-breakdown enzyme, angiotensin I converting enzyme (ACE) 2, suggests the importance of Ang II degradation in hypertension. The present study explored the signaling mechanism by which ACE2 is regulated under hypertensive conditions. Real-time PCR and immunohistochemistry showed that ACE2 mRNA and protein expression levels were high, whereas ACE expression levels were moderate in both normal kidney and heart. In contrast, patients with hypertension showed marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
268
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(294 citation statements)
references
References 35 publications
21
268
2
3
Order By: Relevance
“…Our present findings demonstrate that Ang II, acting through AT 1 R, downregulates ACE2 mRNA expression and activity in the developing kidney. These results are consistent with the findings that Ang II decreases ACE2 gene expression and activity in neonatal cardiomyocytes and in human tubular epithelial (HK-2) cells in vitro through AT 1 R (26,27). Coordinate regulation of ACE and ACE2 by Ang II during postnatal life may represent a dual mechanism by which Ang II prevents its ACE-dependent generation from Ang I as well as inhibits its ACE2-mediated degradation to Ang-(1-7).…”
Section: Ontogeny Of Ace2supporting
confidence: 81%
“…Our present findings demonstrate that Ang II, acting through AT 1 R, downregulates ACE2 mRNA expression and activity in the developing kidney. These results are consistent with the findings that Ang II decreases ACE2 gene expression and activity in neonatal cardiomyocytes and in human tubular epithelial (HK-2) cells in vitro through AT 1 R (26,27). Coordinate regulation of ACE and ACE2 by Ang II during postnatal life may represent a dual mechanism by which Ang II prevents its ACE-dependent generation from Ang I as well as inhibits its ACE2-mediated degradation to Ang-(1-7).…”
Section: Ontogeny Of Ace2supporting
confidence: 81%
“…With the exception of the increased ANG II concentration in PDAC tissue homogenates, we also found that ANG II significantly inhibited ACE2 protein expression in BxPC3 and SW1990 cells. The AT1 receptor-mediated ERK/p38 MAP kinase signaling pathway may be a key mechanism by which ANG II downregulates ACE2 expression (Koka et al 2008). The downregulation of ACE2 by ANG II may serve as a mechanism within the pancreatic tissues to favor ANG II-mediated responses in PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…As a recently reported homologue of ACE, angiotensin converting enzyme 2 (ACE2) is a new component of the updated RAS (Koka et al 2008). This enzyme is highly expressed in the endothelial cells of the heart, kidney, and testis, and mainly degrades ANG II to angiotensin 1-7 (ANG 1-7), which is thought to act as a vasodilator and is involved in apoptosis and growth arrest, in contrast to ACE activity which generates ANG II and degrades ANG 1-9 (Epelman et al 2008;Moon et al 2008;Soler et al 2008).…”
mentioning
confidence: 99%
“…2 Increasing evidence shows that Ace2 has an essential role in the cardiovascular and kidney diseases. 1,3,4 Ace2 inhibition also leads to the development of albuminuria in a mouse model of diabetes.…”
mentioning
confidence: 99%